The Kingdom of the Netherlands-Netherlands : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems, Securities Settlement Systems, and Anti-Money Laundering/Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents findings of Financial System Stability Assessment for the Netherlands, including Reports on the Observance of Standards and Codes on Banking Supervision, Securities Regulation, Insurance Regulation, and Corporate Governance. Overall, the financial system is sound, resilient to potential adverse shocks, and well supervised. Risks both on the international front and domestically appear well within the capacity of the banks to manage them. The pensions sector, though still sensitive to significant equity price reversals, is in a rebuilding stage, underpinned by firm supervisory action.